1990
DOI: 10.1128/jb.172.4.1983-1991.1990
|View full text |Cite
|
Sign up to set email alerts
|

Organization of the replication control region of plasmid ColIb-P9

Abstract: We identified a 1,845-base-pair sequence that contains essential information for the autonomous replication and regulation of the 93-kilobase-pair Inclot group ColIb-P9 plasmid. Biochemical and genetic analyses revealed that this sequence specifies at least two structural genes, designated repZ MATERIALS AND METHODSBacteria, phages, and plasmids. The bacterial strains, phages, and plasmids used are listed in Table 1. E. coli P3478 (polAI) (9) was used to isolate the replication fragments of ColIb-P9. Strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0
1

Year Published

1991
1991
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 42 publications
2
58
0
1
Order By: Relevance
“…In pMU720, it has been shown that increasing the distance between the distal pseudoknot sequence and TIR of repA by as few as 2 bases drastically reduces the expression of this gene (54). The notion that these distances are important for function is supported by the observation that they have been conserved in all of the I-complex plasmids examined to date (13,28,36). On the other hand, the difference in the spacing between the distal pseudoknot sequence and the repB stop codon is less likely to be important, given that the corresponding codon of pMU720 could be moved a considerable distance with little effect on repA expression, as long as the ribosome terminating translation of repB was in a position to disrupt the secondary structure sequestering the distal pseudoknot sequence and TIR of repA without obstructing formation of the pseudoknot (37,53).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In pMU720, it has been shown that increasing the distance between the distal pseudoknot sequence and TIR of repA by as few as 2 bases drastically reduces the expression of this gene (54). The notion that these distances are important for function is supported by the observation that they have been conserved in all of the I-complex plasmids examined to date (13,28,36). On the other hand, the difference in the spacing between the distal pseudoknot sequence and the repB stop codon is less likely to be important, given that the corresponding codon of pMU720 could be moved a considerable distance with little effect on repA expression, as long as the ribosome terminating translation of repB was in a position to disrupt the secondary structure sequestering the distal pseudoknot sequence and TIR of repA without obstructing formation of the pseudoknot (37,53).…”
Section: Discussionsupporting
confidence: 50%
“…For example, replication of the ColE1 plasmids is regulated by an antisense RNA, which by binding to a preprimer RNA alters its folding and prevents its subsequent processing to form a primer for the initiation of DNA synthesis (19,24,49,50). The antisense RNAs of the pT181, FII, IncI 1 and IncB plasmids inhibit the expression of the genes coding for the essential replication initiation proteins (Rep) (13,30,31,35,42,46). In pT181, binding of the antisense alters the folding of the rep mRNA, resulting in transcriptional attenuation of the message (31).…”
mentioning
confidence: 99%
“…Plasmid pDM1, carrying the wild-type argU gene, has been described previously (25), while the 4.5-kb argU10(Ts) HindIII chromosomal fragment (2) was cloned into the vector pBR322 to generate pKC1. Plasmid pAp102 was created by ligating the gene encoding ā¤-lactamase to the 2-kb EcoRI-XbaI fragment containing the sequence essential for autonomous replication of ColIb-P9 (11). The NaeI-VspI fragment of pUC119, which includes the gene encoding the ā£-fragment of lacZ together with the multiple cloning site in it, was cloned into the EcoRI site of pAp102 to generate pCL1.…”
Section: Bacterialmentioning
confidence: 99%
“…The replicons from plasmids belonging to IncB, IncFII, IncFIC, IncI " , IncK, IncL\M and IncZ have been shown to share a common replication control mechanism, namely antisense control, and to share some homology between both DNA and protein sequences (Athanasopoulos et al, 1995 ;Hama et al, 1990 ;Praszkier et al, 1991 ;Saadi et al, 1987). In the IncFII replicon of R1 an antisense RNA molecule (CopA) inhibits synthesis of the replication protein (RepA) by binding to the leader region of the repA mRNA (CopT).…”
Section: Introductionmentioning
confidence: 99%